2003
DOI: 10.1007/s00592-003-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Body composition changes following laparoscopic gastric banding for morbid obesity

Abstract: Most reports of outcome following obesity surgery report weight and co-morbidity changes only. We studied body composition changes in 17 adult patients (15 F, 2 M, age 43+/-2 years, range 28-58 years), with morbid obesity (initial BMI 40.4+/-4.9 kg/m(2), range 34.7-48.8) who were managed surgically by laparoscopically inserting an adjustable gastric band. Body composition was studied before and after surgery (mean interval of 909+/-51 days, range 441-1155 days) using anthropometry (abdominal circumference, AC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…Several studies have evaluated post-LGBS abdominal fat loss using dual-energy X-ray absorptiometry (DEXA) or bioelectrical impedance [28][29][30]. These studies demonstrated significant reductions in relative and absolute amounts of abdominal fat [29] or percent body fat [28,30]. However, DEXA is unable to differentiate between subcutaneous and visceral fat so that the resultant measure of abdominal fat is a combination of both depots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated post-LGBS abdominal fat loss using dual-energy X-ray absorptiometry (DEXA) or bioelectrical impedance [28][29][30]. These studies demonstrated significant reductions in relative and absolute amounts of abdominal fat [29] or percent body fat [28,30]. However, DEXA is unable to differentiate between subcutaneous and visceral fat so that the resultant measure of abdominal fat is a combination of both depots.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is unique in that it clearly links improvements in insulin resistance in LGBS patients to VAT loss rather than to weight loss. Several studies have evaluated post-LGBS abdominal fat loss using dual-energy X-ray absorptiometry (DEXA) or bioelectrical impedance [28][29][30]. These studies demonstrated significant reductions in relative and absolute amounts of abdominal fat [29] or percent body fat [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease was apparently not accompanied by changes in parathyroid hormone (PTH), with some authors even evidencing a significant decrease with a concomitant increase in vitamin D [101]. A lack of effect of AGB on BMD or bone mineral content is consistently found in the literature [102,103]. However, a decrease in femoral and trochanter BMD with no significant changes in total BMD has been reported in one study 24 months after AGB [104].…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 92%
“…1,2 Bariatric surgery with gastric banding induces a substantial weight loss due to a decrease in fat mass with relatively less reduction in the components of fatfree mass, and without significant deleterious effects on body composition. 5,6 In the phase of rapid weight loss that follows gastric banding, there is a preferential mobilization of visceral fat, compared with total and subcutaneous adipose tissue. 7 Restrictive obesity surgery has been shown to result not only in sustained weight loss, but also in improvement in eating behavior.…”
Section: Introductionmentioning
confidence: 99%